"Microsurgical breast reconstruction - a salvage option for failed implant-based breast reconstruction" - Bigdeli, Amir Khosrow; Tee, Jia Wei; Vollbach, Felix Hubertus; Diehm, Yannick; Falkner, Florian; Strübing, Felix; Mahrhofer, Maximilian; Gazyakan, Emre; Kneser, Ulrich; Siegwart, Laura (The breast, 2025)
Background - The objective of this study was to evaluate microsurgical breast reconstruction as a salvage option for patients with failed implant-based breast reconstruction. - Methods - We conducted a retrospective single-center study including all patients with failed unilateral implant-based breast reconstruction who elected to undergo conversion surgery to microsurgical breast reconstruction from January 2015 to December 2023. Patients were grouped according to the urgency for conversion surgery in the urgent (implant infection or extrusion) or elective (capsular contracture, patients’ desire) group. Both groups were compared. - Results - 120 patients were included in the study. 101 patients (84 %) were grouped in the elective group and 19 patients (16 %) in the urgent group. Patient characteristics and intraoperative variables including the utilization of DIEP/MS-TRAM and TMG flap for microsurgical reconstruction were similar in group comparison. Patients in the urgent group had significantly more surgical interventions (3.3 vs. 2.0, p < 0.001) and suffered from significantly more major complications requiring re-operation (32 % vs. 11 %, p = 0.018) compared to the elective group. There was one flap loss in the urgent group (5 % vs. 0 %, p = 0.158). - Conclusion - Microsurgical breast reconstruction is a reliable and safe salvage option in patients with failure of implant-based breast reconstruction. Urgent conversion to microsurgical breast reconstruction due to implant-associated complications, such as infection or extrusion, requires more surgical interventions to achieve successful breast reconstruction and has a higher rate of major complications compared to elective conversion.